Musculoskeletal injuries and the level of somatic constitution and physical fitness of officer cadets at the Military Academy of Land Forces - Dariusz Lenart (Kazimierz Wielki University, 2016)
Purpose. The educational process requires a commitment from officer cadets to develop and maintain physical fitness as a basis for implementing various training tasks. This process is often associated with numerous overloads and musculoskeletal injuries in students. Therefore, the aim of the study was to assess whether injuries and overloads suffered during the training process at the Military Academy of Land Forces differentiated somatic constitution, physical fitness and functional parameters of the respiratory system in the officer cadets. Methods. The research material was gathered as a result of testing officer cadets of the Military Academy of Land Forces in Wrocław in 2011-2015. 89 men were covered by the study. The average age of the examined cadets was 22.9 years. Examinations of the students included anthropometric measurements, physical fitness tests, spirometry and a survey. Results. The results indicate the presence of significant differences in the somatic construction of the officer cadets. Similar physical fitness and the level of the respiratory system efficiency characterized separated groups of students in terms of suffered injuries. Conclusions. Previous injuries turned out to be a factor, which significantly differentiated somatic constitution of the officer cadets. The advantageous, from the health point of view, mean values of the body height, lean body mass, muscle mass and bone mass characterized students, who during the four-year education at the military academy did not suffer musculoskeletal injuries. Past injuries were not also a factor, which substantially diversified the level of functional characteristics.